Network Planning Analysis Using CPM and PERT Methods on Optimization of Time and Cost - Aulia, Surayya; Cipta, Hendra (Sinkron : jurnal dan penelitian teknik informatika, 2023)
The shipbuilding industry is the most important industry to support sea transportation in the context of maritime development. As a company engaged in shipping, the function of the shipyard is as a place for shipbuilding, ship repair, and ship maintenance. One of the activities carried out by PT. DNC as a shipyard company is to repair TK Aek Sigala-gala. Ship repair is a process of repairing or replacing ship materials that cannot be used to avoid risks that occur in the sea when the ship sails. In the implementation of project activities, the company must understand the right network so that there are no problems scheduling, planning and controlling project activities. This study aims to solve the problems faced by the company, is the delay in completion time. The data used is secondary data related to the sequence and relationship of activities, execution time, and cost budget plan (RAB). This study uses CPM and PERT methods to determine the optimal turn around time using critical path and probability concepts. The results of the CPM and PERT methods are activities on the critical path with an optimal duration of 98 days. The crashing method is to reduce the duration to 72 days with savings of Rp. 16,351,708. if the project implementer does not crash, the penalty that must be paid is Rp. 3,072,963,905.